Prevention of Early Reocclusion after Thrombolysis of Copper Coil-induced Thrombi in the Canine Carotid Artery: Comparison of PEG-Hirudin and Unfractionated Heparin - Rübsamen, Klaus; Hornberger, Wilfried (Thrombosis and Haemostasis, 1996)
Cofactor-independent thrombin inhibitors as adjunctive treatment to thrombolysis have been found to enhance reperfusion and reduce the incidence of early reocclusion more effectively than heparins. However, all thrombin inhibitors presently available are rapidly cleared from the circulation which may cause rebound effects after cessation of treatment. To evaluate the effect of PEG-hirudin (LU 87981) a new, long acting derivative of hirudin as adjunctive treatment to rt-PA, a thrombotic occlusion of the carotid artery was induced in mongrel dogs by means of a copper coil. Vessel patency was continuously monitored with an electromagnetic flow probe. Thrombolysis of the occluded artery was induced by administration of 40 Μg × kg−1 + 240 Μg × kg−1 × h−1 rt-PA (low dose) or 80 Μg × kg−1 + 480 Μg × kg−1 × h−1 rt-PA (high dose). With high dose rt-PA treatment, patency was achieved in all animals within 50 min (range 24 to 75), with low dose rt-PA treatment only in 6 out of 8 animals after 73 min (range 26 to 117). Concomitant administration of PEG-hirudin (0.3 mg × kg−1 bolus + 0.15 mg × kg−1 × h−1 infusion) increased the incidence of reperfusion in the low dose rt-PA group to 100% while the reperfusion time was shortened from 73 min in the corresponding control group to 38 min (range 20 to 75 min) in the group given PEG-hirudin (p = 0.065, Mann-Whitney U-test). The carotid artery blood flow, which rapidly declined to zero within 18 to 27 min after discontinuing low or high dose rt-PA infusions remained at a sustained level for the whole observation period of 4 h only in the group given PEG-hirudin. Only one animal reoccluded after 229 min. Unfractionated heparin (UFH) given at a dose of 0.3 mg × kg−1 bolus + 0.3 mg × kg−1 × h−1 infusion did not improve the incidence of reperfusion or lower the incidence of reocclusion. Buccal bleeding time was prolonged after high dose rt-PA treatment and after low dose rt-PA with adjunctive UFH- or PEG-hirudin treatment. Buccal blood loss was not significantly affected by either treatment.In conclusion, these experiments indicate that early reocclusion after thrombolysis can effectively be diminished by concomitant treatment with the long acting thrombin inhibitor PEG-hirudin with moderate effects on bleeding time and aPTT.